PENGARUH PROFITABILITAS, UKURAN BANK, DAN NON-PERFORMING LOAN TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL MEDIASI - Mara, Uli Lasdao; Munandar, Agus (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
This research aims to understand the influence of Bank Profitability, Bank Size, and Non-Performing Loans (NPL) on Company Value, by considering the mediating role of Bank Capital Structure. The population of this research is commercial banks registered on the IDX during the 2018-2022 period which are included in the KBMI 3 category. The method for analyzing this research uses Structural Equation Modeling which is assisted by using SmartPLS statistics software. There were 10 banks that met the research sample criteria, so that the sample obtained was 50 financial reports. The research results show that bank size and NPL have a positive effect on capital structure, while profitability has no effect on capital structure. Furthermore, profitability, bank size have a positive effect on company value, and capital structure has a negative effect on company value. Meanwhile, NPL has no effect on company value. Then, the results of this research also show that capital structure does not mediate the relationship between profitability and NPL and company value. However, capital structure successfully mediates the relationship between bank size and firm value.